Eidolonic Optometry: A Tribute to Dr. Mort Davis. (Optometry & Visual Performance, 2023)
The following three articles appeared as a serial from late 1986 and throught 1987 in the Curriculum distributed by the Optometric Extension Program Foundation. This series, "adds to the concepts developed by A.M. Skeffington, OD, for describing the emergent in his model of vision. The series will be published in its entirety starting in this issue and throughout Volume 10 as a tribute to Dr. Mort Davis, who passed earlier this year. We hope you enjoy his brillaince. The table of contents for this series is: I. Introduction II. The theories behind eidolonic optometry III. The scope of services IV. Tests used to determine the patient's level of development V. Testing directional concepts VI. Testing the guidance system VII. Testing visual cognition VIII. Sports vision IX. Multidisciplinary treatment X. Brain asymmetry and the eidolon XI. Rehabilitative optometry and vision care for senior citizens XII. Summation and conclusions